ANALYSIS OF THE PARENTS’ DIFFICULTIES AS HOME-TEACHERS - Hernandez, Renalyn (International Journal of Arts, Sciences and Education, 2022)
Teachers and parents have been partners for providing child’s educational needs since then. But knowing what the pandemic has caused to the education system, the researchers had come up with the idea of analyzing parents’ difficulties in as home-teachers and put an end to it. This study intends to look over to the impact of online kumustahan to the challenges parents have encountered throughout their teaching experience. In addition, it also focused on the possible solutions to the problems and the effect of online kumustahan to the difficulties encountered by the parents as home-teachers. During the school year 2021-2022, a total of 30 Grade IV pupils’ parents from San Antonio Central School in the Schools Division of Quezon participated in this study. Since it has evolved into a parent-teacher interaction that can enhance a student's education, online kumustahan with parents is important. It can address the difficulties parents encounter when instructing their children at home, and it helps home-teachers find solutions to the issues they have and will face. Based on the study, online kumustahan has a favorable impact on teachers and parents in students learning progress.